Effectiveness and Reformulation of Islamic Religious Education in Schools in the Modern Era - Syamsul Aripin; Nurdiansyah, Nana Meily; Arief, Armai; Yusof, Nabilah binti (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study aims to gain an in-depth understanding of the effectiveness and reformulation of Islamic Religious Education (IRE) in the modern era. Design/methods/approach – The research method used is a literature study with a descriptive qualitative approach. The data sources and data collection techniques used were obtained from books, journals, or scientific articles, and the analysis technique used was content analysis. Findings – The results of the study show that, first, changes to Islamic Religious Education in the modern era are very complex, because the elements of modernity continue to undergo changes in terms of teaching, material, methods, and approaches. The effectiveness of Islamic Religious Education (IRE) in the modern era requires a reformulation of learning that is contextual and adaptive. Therefore, the differences that arise due to the development of science and technology need to be seen as a gift that enriches comprehensive and holistic understanding; second, learning is directed at solving the problems of modernity faced by Muslims through scientific, social, and religious approaches; third, the delivery of Islamic knowledge is not dogmatic, but emphasizes historical analysis so that students are able to understand the dynamics of the development of Islamic teachings; fourth, text-based learning methods must be balanced with critical analysis of social realities to make them more applicable; fifth, strengthening the spiritual dimension through Sufism is a fundamental requirement in shaping religious character; sixth, the effectiveness of Islamic Education is not only measured by individual piety, but also by its contribution to building social piety.    Research implications/limitations – Data sources are limited to online and offline scientific literature based on literature reviews as the primary source. Future researchers can use more in-depth techniques and methods such as research and development or case studies. Originality/value – The results of this study provide knowledge and implications for IRE teaching models and their reformulation to contribute to the challenges and progress of the times, so that synergy between various transformations can be achieved.